DIDACTIC FUNDAMENTALS OF THE COGNITIVE ORGANIZATION STUDENT ACTIVITIES (Pedagogy of Higher and Secondary Education, 2008)
In article the interrelation educational and knowledge activity of the students is opened, the features of educational activity of the students from positions activity approach are determined.